Environmental law in Anthropocene epoch - Janet Blake; Amir Panahande Somarein (علوم محیطی)
Introduction: In recent years, the ‘Anthropocene Working Group’ under Jan Zalasiewicz’s direction, has played an extremely significant role in the explanation of the ‘Anthropocene epoch’ from a scientific point of view, by publishing numerous articles on this issue. Among the authors of these papers, Vidas is one of the most important lawyers who has published papers concerning the relationship between the Anthropocene and international law. This article aimed to explain introductory subjects about the Anthropocene and their connection with environmental law, which has no history in the Persian language literature.  Material and methods: In this paper, the latest scientific data along with new approaches used by environmental lawyers will be studied. Recent global environmental changes suggest that the Earth has arrived at a new geological epoch under the influence of mankind. ‘Biodiversity’ and ‘climate change’ are two subjects that are mostly protected by environmental law in this new epoch since they are severely affected by the consequences of changes in the Earth’s ecosystem. Results and discussion: Many lawyers believe that environmental law and governance issues are the result of the ‘Holocene’ stability, and understanding the relationship between human beings and the environment seemed relatively simple and the centrality of humans and governments was fixated. While in the Anthropocene epoch, there is less stability and predictability, and in order to restore the integrity to the Earth’s ecosystem, giving centrality to human governments must be replaced with an ‘eco-centric’ approach in international and national laws. Conclusion: One of the principles that should be emphasized in international treaties is taking responsibility for the conservation of the environment’s integrity. If the principle of ‘sovereignty over natural resources’ is a Jus Cogens in international law, then the state’s responsibility towards the ‘conservation of natural resources’ and ‘safeguarding the ecological integrity’ should be a strong obligation. This paper proposes that a declaration on fundamental principles of environmental law should be presented, in which some guiding principles regarding the rights and duties of humankind in relation to the environment in the new epoch could be codified.